A comprehensive review on planar boron nitride nanomaterials: From 2D nanosheets towards 0D quantum dots. (February 2022) - Angizi, Shayan; Alem, Sayed Ali Ahmad; Hasanzadeh Azar, Mahdi; Shayeganfar, Farzaneh; Manning, Max I.; Hatamie, Amir; Pakdel, Amir; Simchi, Abdolreza
Abstract: Moving from two-dimensional hexagonal boron nitride (2D h-BN) flatlands towards their quantum sized zero-dimensional (0D) islands, as the newest member of the h-BN family, has recently opened up novel research areas due to the emergence of unique optical and physicochemical properties, excellent thermal and chemical stability, and desirable biocompatibility. This review elaborates on the fundamental properties of 2D and 0D h-BN nanomaterials and covers the latest progress in the fabrication and applications of BN nanosheets (BNNSs) and quantum dots (BNQDs). Initially, the transformation of properties in h-BN nanomaterials is discussed when moving from the 2D realm towards the 0D quantum zone. Then, top-down and bottom-up synthesis methods of 2D h-BN are reviewed, analyzing each method's advantages and shortcomings. The review will continue explaining the fabrication methods of BNQDs and the impact of synthesis technique on their physiochemical characteristics. Special attention is given to surface chemistry of BNQD nanocrystals that can alter their electronic band structure and optoelectronic properties. Thereafter, detailed discussion on the implementation of BNNSs and BNQDs in various applications, e.g., catalysts, sensors, bioimaging probes, proton exchange membranes, and photocatalytic activators, is provided. At last, an overview of the ongoing challenges and future directions for BNQD research is presented.